Cirrhosis and term pregnancy: gastrointestinal bleeding and fetal death, caesarean section and portocaval anastomosis - Praderi, Raúl; Mazza, Milton; Camacho de Osorio, Olga; Peri, Lorenzo (Cirugía del Uruguay, 2020)
The paper presents the results of the observation of ci rrhosis of the liver with portal hipertension and serious digestive hemorrhage due to rupture of esophagogastric varices in a patient with an eightmonth pregnancy. A caesarean (extraction of the dead fetus) as well as anastomosis termino lateral porto-cava, was performed in the same surgical procedure. The association cirrhosis-pregnancy and the sur'gical tactics employed, are discussed.